Effect of nano-bainite microstructure and residual stress on friction properties of M50 bearing steel. (January 2022) - Yu, X.F.; Wei, Y.H.; Zheng, D.Y.; Shen, X.Y.; Su, Y.; Xia, Y.Z.; Liu, Y.B.
Abstract: By means of the measurement of the residual stress and friction properties, the observation of the microstructure by the SEM, the X-ray diffraction (XRD) was used to phase analysis and the nano-bainite structure was determined by transmission electron microscopy (TEM). The effect of nano-bainite microstructure and residual stress on friction properties of M50 bearing steel was analyzed after austempered at 200 °C for 2 h, 16 h and 32 h. Results show that nano-bainite structure is composed of thin film austenite and bainite ferrite, the mean thickness of bainite ferrite lath is about 90 ± 10 nm. The contents of nano-bainite are 15.772%, 33.951% and 50.332% respectively after austempered for 2 h, 16 h and 32 h. The hardness increases from 2 to 16 h, which is related to the precipitation of secondary carbides in bainite. And the hardness decreases after 16 h due to the fact that the bainite content is the largest. The fluctuation range of the residual stress of the sample austempered for 32 h + tempering is the smallest and the distribution is the most uniform. Wear resistance of the sample gradually increases with the extension of austempering time which is mainly related to hardness, residual stress state and thermal stability.